Assessing The Impacts Of Climate Change On Desertification In Niger State, Nigeria - Grace Jude Idoko (Journal of Social Research, 2024)
This study explores the impacts of climate change on desertification in Niger State, Nigeria. Desertification, exacerbated by climate change, poses significant challenges to ecosystems and communities in Niger State, Nigeria. This study examines the key drivers of desertification, its socio-economic impacts, and the effectiveness of adaptation and mitigation strategies. A survey was conducted among 120 respondents, revealing overgrazing and climate change-induced factors as the primary drivers of desertification, with deforestation, poor land management practices, and urbanization also playing significant roles. Respondents highlighted the complex interactions between climate change-induced factors, such as changes in rainfall patterns and increased temperatures, and their contribution to desertification processes. The socio-economic impacts of desertification were pronounced, including water scarcity, decreased agricultural productivity, increased poverty, and loss of biodiversity. While some adaptation and mitigation strategies are being implemented, there is a need for greater community involvement, policy support, and integrated approaches to enhance resilience and promote sustainable land management practices. These findings underscore the urgency of coordinated action to address desertification in Niger State, Nigeria, emphasizing the importance of holistic strategies that integrate climate change adaptation, sustainable development, and community empowerment.